2018
DOI: 10.1002/jso.25112
|View full text |Cite
|
Sign up to set email alerts
|

Comparative outcomes of adenosquamous carcinoma of the pancreas: An analysis of the National Cancer Database

Abstract: Although patients with ASCP and PDAC tumors have similar survival when non-surgical and surgical patients are combined, ASCP is associated with worse survival in stage I/II resected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 35 publications
(68 reference statements)
4
51
0
Order By: Relevance
“…These relatively rare tumors are larger and more commonly found in the body or tail of the pancreas. An analysis of the National Cancer Database revealed that adenosquamous carcinoma of the pancreas is associated with worse outcome in stage I/II resected patients when compared to pancreatic adenocarcinoma …”
Section: Discussionmentioning
confidence: 99%
“…These relatively rare tumors are larger and more commonly found in the body or tail of the pancreas. An analysis of the National Cancer Database revealed that adenosquamous carcinoma of the pancreas is associated with worse outcome in stage I/II resected patients when compared to pancreatic adenocarcinoma …”
Section: Discussionmentioning
confidence: 99%
“…Pancreatic cancer is a very aggressive malignancy with a very poor prognosis a 5-year survival rate of only 1-9.2%, and more than half of patients already have distant metastases at diagnosis (1)(2)(3)(4). Among the pancreatic cancer, pancreatic ductal adenocarcinoma (PDAC) is the most common, accounting for about 85%, and pancreatic adenosquamous cell carcinoma (PASC) is a rare type, accounting for only 1-4% (1,2,5). It is clearly known that the prognosis of PASC is much worse than PDAC, and even in resected patients the median survival is only 5-14.8 months (1,2,(5)(6)(7)(8)(9)(10)(11).…”
Section: Examine the Clinicopathological Features Of Pancreatic Adenomentioning
confidence: 99%
“…Data on primary pancreatic SCC and A‐SCC are sparse, as they represent only 0.5%‐2%, and 5%, of pancreatic neoplasms, respectively . Incidence rates for primary pancreatic SCC and A‐SCC are increasing .…”
Section: Introductionmentioning
confidence: 99%
“…6 Data on primary pancreatic SCC and A-SCC are sparse, as they represent only 0.5%-2%, and 5%, of pancreatic neoplasms, respectively. 7,8 Incidence rates for primary pancreatic SCC and A-SCC are increasing. 9 The prognosis for primary pancreatic SCC is thought to be poor compared with AC; however, this is based primarily on case reports and small case series.…”
Section: Introductionmentioning
confidence: 99%